2014
DOI: 10.1097/iae.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Steroid-Induced Ocular Hypertension After Vitreoretinal Surgery With Difluprednate Versus Prednisolone Acetate

Abstract: Eyes treated with DP after vitreoretinal surgery were at increased risk for developing clinically significant increases in IOP compared with those receiving PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…The data from this study confirmed earlier reports showing an increase in IOP when DFBA is compared to PA 25,28,30. Importantly, in this study, the mean IOP remained ≤21 mmHg for both PA and DFBA patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The data from this study confirmed earlier reports showing an increase in IOP when DFBA is compared to PA 25,28,30. Importantly, in this study, the mean IOP remained ≤21 mmHg for both PA and DFBA patients.…”
Section: Discussionsupporting
confidence: 91%
“…Jeng et al conducted a retrospective chart review of 100 patients treated with either PA or DFBA after vitreoretinal surgery where patients received PA or DFBA four times a day for a minimum of 1 month. Similar to this present study, the authors found that compared to PA-treated patients, DFBA-treated patients had a significantly higher percentage of patients with an IOP of ≥21 mmHg and an increase from baseline of >10 mmHg 28. The percentages were higher in the study conducted by Jeng et al possibly related to the higher steroid dosage used (four times a day for 1 month).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…20,21 Elevated IOP is a known potential adverse reaction to steroid use, 22 and is listed in the warnings section of the package insert for this drug class. Based upon previous experience with topical ocular steroids, class labelling, and the characteristics of the patient population in the current study, the incidence of increased IOP is not unexpected.…”
Section: Discussionmentioning
confidence: 99%